EVALUATING SOIL DEGRADATION IN SHWAN AND ALTUN KOPRI AREAS IN KIRKUK GOVERNORATE BY SOME SPECTRAL INDICATORS - A. E. Ibrahim; D. R Azeez (مجلة الأنبار للعلوم الزراعية)
The study aims to assess soil degradation the northeastern part of Kirkuk Governorate includes the districts of (Shwan) and (Altun Kopri) extends between longitudes (44̊ 22ʹ 29ʺ-44̊ 38ʹ 22ʺ) and latitudes (35̊ 42ʹ16ʺ-35̊ 43ʹ 53ʺ) with a total area of (117,683.96 hectares). Spectral comparative indicators for the years (1997, 2014, 2020, 2023) were used to monitor the deterioration during these years using landsat 5 MSS, landsat 8 OLI and Arc GIS 10.4.1 software for mapping. The NDVI (low vegetation) decreased in 2023 compared to 1997, while the percentage of (medium vegetation) and (dense vegetation) in 2023 increased compared to previous years., As for the SAVI, class (very few) has decreased its area in 2023 compared to 1997, while for the rest of classes (few), (moderate), (good) and (very good), their areas have increased in 2023 compared to previous years. As for CI class, the (medium) class increased in 2023 compared to 1997, while the (strong) class was the opposite of the aforementioned class, as it decreased in 2023 compared to previous years, As for the BSI, the (no degradation), as it decreased in 2023 compared to 1997, while the class (little degradation) increased in 2023 compared to previous years, while the class (medium degradation) increased its percentage compared to 1997, As for the NDMI indicator, the class (dry lands) in the year 2023 has decreased compared to 1997, as for the second class (low moisture lands), a noticeable increase was observed in the year 2023 compared to 1997